Consumer Debt Management Options - Lisa M. Leslie; Elaine Courtney; Julie England; Michael S. Gutter (EDIS)
When a consumer has unwanted debt or high amounts of debt, there are different options that can help eliminate or decrease their debt level. However, it is important to choose the right option. This 5-page fact sheet describes some of the debt-management options that are available to consumers. Written by Lisa M. Leslie, Elaine Courtney, Julie England, and Michael S. Gutter, and published by the UF Department of Family, Youth and Community Sciences, February 2012.